Antimicrobial Efficacy of Smear Clear in the Elimination of Enterococcus faecalis. An In Vitro Study - Alvear-Pérez, Javier (2026)
Microorganisms are fundamental etiological factors in pulpal and periapical diseases. Enterococcus faecalis, a Gram-positive facultative anaerobic coccus, can penetrate dentinal tubules and survive chemical-mechanical instrumentation. Endodontic success requires effective irrigation to reach areas inaccessible to instruments. Despite sodium hypochlorite's antimicrobial efficacy, its toxicity necessitates exploring alternatives.  To evaluate Smear Clear®'s antimicrobial efficacy against E. faecalis. This in vitro study tested Smear Clear® against E. faecalis (ATCC 29212®) strain, determining its antimicrobial efficacy and establishing minimum inhibitory and bactericidal concentrations. Bacterial sensitivity was tested using microplate dilution techniques with appropriate controls. Smear Clear® at 100% showed bactericidal activity against E. faecalis. At 50% concentration, it demonstrated the minimum concentration needed for growth inhibition with bacteriostatic properties. Smear Clear® exhibits antimicrobial properties against E. faecalis and represents a potential alternative to sodium hypochlorite in endodontic irrigation, with its components, particularly cetrimide, directly affecting bacterial sensitivity.